Difference Between Men and Women in Drug Use Disorders - Griffith, Clairmont; France, Bernice La (Archives of Clinical and Medical Case Reports, 2019)
For a long time, drug-abuse disorders were related to men. Women were less involved in drug abuse. They were even not allowed to speak about it openly. Nonetheless, in the last ten years, there has been great transformation resulting in increased drug use among women. However, despite the changes, contemporary clinical practice is greatly dominated by male studies irrespective of the succinct differences in drug use disorders between the men and the women. Therefore, the main objective of the research is to bridge the gap by discussing the differences between men and women in drug use disorders. Using eight novel studies, the research examines the variances pointing out clear differences between the men and women. The study discovered that gender differences are similar for all drug use disorders. The reviews revealed that women are more likely to get addicted compared to men. Additionally, their escalation is much quicker than that of men. Women stabilize at higher doses while men stabilize at minimal doses. Moreover, the side-effects of drugs are higher in women than men. Also, women are more susceptible to relapse than men.